The Implementation of Cooperative Learning Method using STAD Technique In Order To Increase Activity and The Studentâ€™s Study Outcome - Hidayatullah, Ainur Rofiq (Classroom Action Research Journal (CARJO), 2018)
The author did observation in class X IPS that have been held in Senior High School 1 Turen, Malang regency, based on the observation during learning process, the student were pasive. They only gave less respond during learning process. Based on the intervierw with Ms. Etika Dewi Rahmawati, known as teacher economy subject, she explain the reasons why the student have low outcomeÂ  because they are less active during learning process. Through the interview and the observation wich has been done, so that we need to solve that problem by changing the fundamental of learning process. Cooperative methode technique STAD can help student to increase their activity in the class. This type of research is PTK (Research Action Class) that consist of two cycles, every cycles has 4 steps: (1) planning, (2) implementation, (3) observation, and (4) reflection. The subject in this research is class XIPS 2, the amount of the subject are 33 student. The learnng material which are used in this reseach are central bank, payment system and the instrumental of payment. This research is held at second semester in Januari 2017. The instrument of this research are observation sheet and test to evaluate learning outcome. The result of this reseach show that the learning process with the aplication of using learning methode technique STAD, generally can make student more active. The average of their activity in the first cycle is 62.40% and in the second cycle is 79,31%. It aslo occurs the increasing of learning outcome, in the first cycle is 45,45% and in the second cycle is 90,32%.